Design, synthesis, and herbicidal activity of indole-3-carboxylic acid derivatives as potential transport inhibitor response 1 antagonists - Wang, Xing; Luo, Mu-Jia; Wang, Yu-Xuan; Han, Wen-Qing; Miu, Jian-Xin; Luo, Xi-Ping; Zhang, Ai-Dong; Kuang, Yi (Frontiers in Chemistry, 2022)
Auxins as an important class of phytohormones play essential roles in plant life cycle; therefore, developing compounds with auxin-like properties for plant growth regulation and weed control applications is of great significance. Herein, we reported the design, synthesis, and herbicidal activity evaluation of a series of novel indole-3-carboxylic acid derivatives as auxin receptor protein TIR1 antagonists. Petri dish herbicidal activity assay demonstrated that most of the as-synthesized target compounds exhibited good-to-excellent inhibition effects (60–97% inhibitory rates) on roots and shoots of both dicotyledonous rape (B. napus) and monocotyledonous barnyard grass (E. crus-galli). The inhibition rates of compounds 10d and 10h reached up to 96% and 95% for the root of rape (B. napus) at 100 mg/L, and they also maintained 92% and 93% inhibition rates even if at 10 mg/L, respectively. Molecular docking revealed that the interactions between these synthesized target compounds and TIR1 protein include tight π–π stacking, hydrogen bond, and hydrophobic interactions. This work expands the range of auxin chemistry for the development of new auxin mimic herbicides.